Niemann - Pick Disease Type B: A Case Report (Bangladesh Journal of Child Health, 2018)
Niemann-Pick disease is a rare lysosomal storage disease responsible for numerous cytological abnormalities involving liver, spleen, lymph nodes, nervous system, lungs and bone marrow. This disease occurs due to accumulation of sphingomyelin in various tissues. Our patient is a 4 years boy presented with hepatosplenomegaly and growth failure. Cherry red spot was found on ophthalmologic examination. Niemann Pick cell was found on bone marrow examination. As because enzyme estimation is not available in Bangladesh, we diagnosed the case as Niemann Pick disease considering the clinical and laboratory findings.Bangladesh J Child Health 2017; VOL 41 (2) :135-137